Meningkatkan Minat Belajar Anak dimasa Pandemi Covid-19 - Marthin Nainggolan; Mia Aulina Lubis (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Field Work Practice or what is often called PKL is a form of organizing educational and training activities by working directly, systematically and directed with competent supervision. PKL is carried out to meet the needs of a professional workforce and is expected to apply the knowledge gained, as well as to be practiced by PKL participants in the world of work. PKL can be carried out by students, students and new workers. At the student level, PKL is implemented systematically by synchronizing education programs at universities with mastery of skills programs obtained through work activities directly in the world of work. To achieve a certain level of expertise, street vendors are held which in student language are usually called internships. On this occasion one of the University of North Sumatra students named Marthin Juanto Parsaoran Nainggolan, Social Welfare Science, Faculty of Social and Political Sciences carried out street vendors at the Solaya Orphanage (PASO). ). Where this field work practice is also guided by the School Supervisor Ms. Malida Putri, S.Sos, M.Kesos and monitored by Mr. Fajar Utama Ritonga, S.Sos., M.Kesos.